Hepatic resection for the right hepatic vein drainage area with indocyanine green fluorescent imaging navigation. (17th March 2020) - Kubo, Norio; Araki, Kenichiro; Harimoto, Norifumi; Ishii, Norihiro; Tsukagoshi, Mariko; Igarashi, Takamichi; Watanabe, Akira; Shirabe, Ken
Abstract: Background/Purpose: Right hepatic vein (RHV) drainage area resection is performed for intrahepatic tumors. However, borders of RHV drainage areas are difficult to identify. We evaluated the usefulness of indocyanine green (ICG) fluorescent images to identify the borders for RHV drainage area resection. Methods: From January 2016 to May 2019, we included 12 patients who underwent hepatic resection of the RHV drainage area, which was evaluated using ICG fluorescence images after clamping the RHV and with or without clamping the proper hepatic artery (PHA). The resected liver volume was compared with the preoperative simulated resected liver volume by 3‐dimensional computed tomography. Results: Eleven borders of the RHV drainage area between the middle hepatic vein (MHV) or inferior RHV drainage area were confirmed using ICG fluorescent images in 12 patients. The borders were observable by only clamping the RHV. In one patient, the border could not be identified because there was a shunt between the RHV and MHV at the peripheral area. Resected liver volume was significantly correlated with the results of preoperative simulation. Conclusion: The RHV drainage area resection could be one of the options of hepatic resection for the tumor involving the root of the RHV. ICG fluorescent imaging in hepatic resection of the RHV drainage area is useful for determining areas of liver congestion and clamping the PHA is not always necessary. Abstract : Highlight Kubo et al evaluated right hepatic vein drainage area resection as an option for resection of the posterior segment and dorsal area of the anterior segment. Indocyanine green fluorescence imaging of the right hepatic vein drainage area was useful as an intraoperative navigation method for determining the area of congestion.